Various analytical methods for analysis of atorvastatin: A review: ANALYTICAL METHODS FOR ANALYSIS OF ATORVASTATIN: A REVIEW - Chawla, Pooja A; Pandey, Shailendra; Monika (Journal of Drug Delivery and Therapeutics, 2019)
Hyperlipidemia is produced due to abnormal elevated level of lipids in the blood and is a major risk factor for many heart diseases such as atherosclerosis and stroke.  Lipids have been implicated in the development of atherosclerosis in humans. In hyperlipidemia there are increased levels of both LDL and triglycerides. Treatment of hyperlipidemia with statins has become an integral part of management of vascular diseases. Statins are the first line therapy for lowering lipid levels. Among statins atorvastatin is the most effective and currently available antihyperlipidemic drug. An enzyme 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase play an important for endogenous cholesterol synthesis. Atorvastatin is HMG-CoA (3-hydroxy-3-methyl-glutaryl-CoA) reductase inhibitor which significantly reduces the lipid levels (low-density lipoprotein, triglycerides, very low-density lipoprotein) and also increases the HDL (high-density lipoprotein) levels. Various analytical methods such as reverse phase high-performance liquid chromatography (RP-HPLC), high performance thin layer chromatography (HPTLC), thin layer chromatography (TLC), ultra-performance liquid chromatography (UPLC), liquid chromatography tendam mass spectroscopy, near infrared spectroscopy, capillary electrophoresis (CE), spectrophotometric methods for determination of atorvastatin as single and in combination with other drugs have been reported.  In this review an attempt has been made to covers all the recent analytical methods which has been used for analysis of atorvastatin.Keywords: Atorvastatin, Analytical Methods, HPLC, HPTLC.